Antibacterial activity of Weissella confusa by disc diffusion method - Krishnan, Manigandan; Dey, Debasish Kumar; Sharma, Chanchal; Kang, Sun Chul (Bangladesh Journal of Pharmacology, 2019)
A visual experiment was conducted to investigate the antimicrobial potential of cell-free culture supernatant of Weissella confusa (DD_A7) against the foodborne pathogenic bacteria Escherichia coli 0157: H7 by disc diffusion method. The result revealed that DD_A7 exerted effective antibacterial potential to control the growth of E. coli upon treatment with 100 µg/mL of the culture supernatant. This study demonstrated that DD_A7 is a potent probiotic candidate to reduce the risk factor associated with Shiga toxin-producing E. coli. Video Clip of Methodology: Duration: 9 min 20 sec Full Screen Alternate